An overview of MPI characteristics of exascale proxy applications - Klenk, Benjamin; Fröning, Holger (High Performance Computing, 2017)
The scale of applications and computing systems is tremendously increasing and needs to increase even more to realize exascale systems. As the number of nodes keeps growing, communication has become key to high performance.The Message Passing Interface (MPI) has evolved to the de facto standard for inter-node data transfers. Consequently, MPI is well suited to serve as proxy for an analysis of communication characteristics of exascale proxy applications.This work presents characteristics like time spent in certain operations, point-to-point versus collective communication, and message sizes and rates, gathered from a comprehensive trace analysis. We provide an understanding of how applications use MPI to exploit node-level parallelism, always with respect to scalability, and also locate parts which require more optimization. We emphasize on the analysis of the message matching and report queue lengths and associated matching rates.It is shown that most data is transferred via point-to-point operations, but the most time is spent in collectives. Message matching rates significantly depend on the length of message queues, which tend to increase with the number of processes. As messages are also become smaller, the matching is important to high message rates in large-scale applications.
Gesehen am 30.08.2017
Keywords: Konferenzschrift